Protest: is a matter of public policies, isn't a matter of police - Penido, Ana (2023)
The article has as its object specific public policies for social protest environments with a view to preventing human rights violations. It is based on the principle that the right to protest is a fundamental human right, and that eliminating social protests is impossible and, furthermore, undesirable. The chosen methodology was the analysis of international regulations and recommendations on the subject in the light of critical literature. Its results were organized into five topics for the construction of regulations at the national level: the need for prior authorization for implementation; responsibility of organizers; participation of politically marginalized groups; performance of communicators; measures for and about the performance of security forces. In its conclusion, the article offers 40 good measures synthesized from international formulations.